Pattern of respiratory diseases among human immunodeficiency virus-infected children in Enugu, Nigeria - C Ayuk, Adaeze; C Ubesie, Agozie; K Iloh, Kenechukwu; Obumneme-Anyim, Ijeoma N; J Emodi, Ifeoma; S Ibeziako, Ngozi; J Anikene, Chukwuemeka; J Enemuo, Eziamaka; Iloh, Ogochukwu; Nwogu, Uloma (Indian Journal of Child Health, 2019)
Introduction: The lung is a major target for infectious and non-infectious complications of human immunodeficiency virus (HIV) infection. Objective: This study sought to assess the prevalence and pattern of respiratory diseases among HIV-infected children attending our pediatric HIV specialist clinic. Methods: A 10-year retrospective review of data on HIV-infected children seen at the Paediatric HIV clinic of the University of Nigeria Teaching Hospital, Ituku/Ozalla, Enugu. HIV diagnosis was made by HIV-DNA polymerase chain reaction testing and antibody testing depending on the age of the child. Diagnosis of pneumonia was made using the WHO pneumonia clinical algorithm while pulmonary tuberculosis (PTB) was diagnosed using clinical and radiological criteria. Data analyses were done with Statistical Package for the Social Sciences version 19 (Chicago, IL). Results: A total of 555 HIV-infected children were analyzed. There were 277 males (49.9%) with male to female ratio of 0.9–1. The cough was the most common complaint in 51.9% of the children. There were 327 respiratory cases observed in 181 of 555 (34.7%) of the children. Using clinical symptoms, 65 of 327 (9.9%) of study participants had upper airway-related diseases with otitis media being most predominant (27/65; 41.5%); pneumonia was reported in 146 of 327 (45%) and PTB in 115 of 327 (35%). Total 124 of 181 children (72.5%) with respiratory infections compared to 18 of 287 (6.3%) without infections had an abnormal chest X-ray (CXR) (p<0.001). Identified risk factors for developing respiratory disease were low socio-economic status, being on second-line highly active antiretroviral therapy and having an abnormal CXR finding. Conclusions: Pneumonia and PTB are common in children with HIV. Chronic radiological change is more common among HIV-infected children with clinical features of respiratory pathology. The need for close lung function monitoring in children with HIV is recommended for early detection of morbidity associated with these infections.